Pre-COVID19: knowledge and level of vaccine acceptance among university students - Yip, Chee Wai; Ain Nor Aliya Zulhelmi,; Muhammad Iqbal Abu Latiffi,; Nazlina Ibrahim,; Mohamad Rahim Kamaluddin,; Jaya Kumar Murthy,; Muhammad Arif Yahya,; Maryam Azlan,; Nur Kareelawati Abd Karim,; Herryawan Ryadi Eziwar Diyari,; Mohd Hanafy Gausmian,; Mohd Ridzwan Yaakub,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Vaccine confers acquired active immunity against many diseases. The emergence of anti-vaccine groups has reinstated the outbreak of many vaccine preventable diseases (VPD), which was once thought to be eradicated from the face of earth, mostly due to ever-present misinformation and disinformation spread through various channels of communications. Hence, public awareness on immunization is vital to prevent the re-emergence of VPD. In this study, we targeted students from Universiti Kebangsaan Malaysia (UKM) and aimed to obtain the level of awareness and perception regarding vaccination among these students. We acquired information on the knowledge of vaccines and the degree of acceptance of vaccines among the university students, and through educational intervention, including the Islamic view on vaccination, we aimed to increase their awareness on immunization and the adverse effects of anti-vaccination. The questionnaires used in the present study were validated by reliability analysis. The study was conducted for a duration of four months, from January to April 2019. A total of 929 respondents were interviewed, and the degree of acceptance on vaccination was at satisfactory level, and none of the students rejected vaccination. Out of 929 respondents, 36 attended the vaccine workshop to undergo the educational intervention, and were asked to refill the questionnaires, and the results of pre- and post-workshop questionnaires were compared. Vaccine workshop successfully improved the knowledge and awareness of the participants on vaccines. The number of participants who can explain herd immunity has also increased. However, there were participants who still believed that vaccine-related information retrieved from social media can be trusted without consideration. Therefore, educational intervention is suggested to be used in public as a tool to combat the expansion of the anti-vaccination community since it was shown to give positive outcomes among the students.